Comparative Analysis of Voice Quality on iLBC and Speex Codecs Server PBX with Voice Comparison Method - Reza Afrida Dewanti; Martono Dwi Atmaja; Nanak Zakaria (Politeknik Negeri Malang, 2022)
VoIP servers provide several types of codecs including iLBC and Speex codecs, each type of codec has a different capacity and quality- different. So that in the process of choosing a codec implementation, VoIP becomes one of the things that affect the quality of communication. The iLBC and Speex codecs are intended for high quality but bitrate . By comparing iLBC and Speex communication, VoIP hoped that the better performance between the two codecs would communicate VoIP based on Quality of Service (QoS) and analyze the audio results of VoIP for voice quality analysis using the voice comparison method using Matlab. Based on the results of the research between the iLBC and Speex parameter value QoS including delay codec speex is smaller than iLBC codec of 31.12 ms. The jitter value of the iLBC and speex is the same, namely 0.01. The packet loss value of the iLBC codec is smaller than the speex codec of 6.18%. The results of the sound quality test in matlab using the sound comparison method showed that the delta amplitude codec speex value was smaller than iLBC codec of 0.00004551 volts.